Capital Structure Among Secondary Sectors of Indonesian Firms : Does Business Scale Matter? - Cahyono, Satriyo Budi; Chawla, Arvinder Singh (Indian Journal of Finance, 2021)
In this study, we analyzed the associations between financial structures and their determinants across different firm scales, that is, large firms (listed in the Main Board Index - MBX) and medium capitalized firms (listed in Development Board Index - DBX) among secondary sectors, namely: basic industry, miscellaneous industry, and consumer goods industry, within the Indonesian capital market during the period from 2005 – 2016. The six explanatory variables, that is, firm size, growth opportunity, profitability, tangibility, liquidity, and business risks were employed to explain financing decisions across different firm scales. Using data panel analysis, we found that the associations between leverages and determinants diverged across different firm scales amongst secondary sectors, as the industry characteristics controlled the relationship mechanisms. In general, profitability and tangibility had essential roles in leverage determination, although these variables were more influential for large firms. Further, the pecking order theory was more influential in explaining the financing behavior of both types of firms. Nevertheless, there was no evidence to deny the applicability of trade-off theory and agency theory. Indeed, the pecking order hypothesis seemed more pronounced for large firms compared to medium-scale businesses among secondary sectors.